Analysis of Learning Outcome Achievements and Support of Lecturer Competencies towards International Accreditation - Nursaadah, Euis; Maisarah, Ira; Wiwit, Wiwit; Syafriadin, Syafryadin; Chandra, I Nyoman (Faculty of Educational Sciences, Universitas Negeri Yogyakarta, 2024)
Learning Outcome (LO) is a formulation of learning outcomes expected to be met by students. LO is structured to equip the competencies that graduates want to achieve. Each course in a program carries LO content that students must achieve. Through the Semester Learning Plan (RPS) prepared by expert lecturers, it will be seen how the LO is provided through the learning process and how to measure it. This study aims to analyze the achievement of LO in 8 (eight) Study Programs at the University of Bengkulu's FKIP which are being proposed for international accreditation. This LO achievement analysis is also linked to the competence of lecturers. The LO used by the 8 Study Programs to meet the requirements of the IQF is in line with international frameworks, one of which is the Europian Qualification Framework (EQF). Therefore, the results of this study support the quality assurance of a program or institution in achieving one of the components of international accreditation. The results of this study found that the scientific fields of the lecturers in each study program were in accordance with the qualifications (qualified) and could be accounted for which was strengthened by the fact that almost all lecturers had the status of certified lecturers. This is supported by the number of reputable national and international publications, scientific works that are registered with copyrights, works in the form of books or book chapters that are registered with ISBNs and others. In addition, learning outcomes have been measured in each program and show readiness towards international accreditation.